PERAN PENGASUHAN KELUARGA DALAM PERKEMBANGAN EMOSI ANAK SAAT BERINTERAKSI SOSIAL - Hasanah, Maria Ulfa; Mahmudah, Ummi (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
This study aims to: 1) knowing the emotial development of children when they are socially interacting. 2) knowing is there the role of family parenting in the emotional development of childrens when they are socially interacting. This qualitative descriptive study, held in three families located at Jl. Pengkeran RT 001/RW 002, Jl. Gabah Sinawur RT 003/RW 001 and Jl. Sukomino RT 001/RW 002, Demangan Village, Siman District, Ponorogo Regency. That familys was chosen as the object of research because family members consisting of father, mother, grandfather and grandmother live in one house involved in childcare. The researchers obtained data by interviewing and directly observing childcare patterns in the three families. This research results: 1) The development of children's emotions is very influential on the process of social interaction. Both pleasant and unpleasant emotions, all of them have their own impact on children in establishing social relations with the surrounding environment. 2) There is a very important role of family parenting in supporting the emotional development of children to be able to interact socially well.